Children’s Particulate Matter Exposure Characterization as Part of the New Hampshire Birth Cohort Study - Jonathan Thornburg (MDPI AG, 2021)
As part of the New Hampshire Birth Cohort Study, children 3 to 5 years of age participated in a personal PM2.5 exposure study. This paper characterizes the personal PM2.5 exposure and protocol compliance measured with a wearable sensor. The MicroPEM™ collected personal continuous and integrated measures of PM2.5 exposure and compliance data on 272 children. PM2.5, black carbon (BC), and brown carbon tobacco smoke (BrC-ETS) exposure was measured from the filters. We performed a multivariate analysis of woodstove presence and other factors that influenced PM2.5, BC, and BrC exposures. We collected valid exposure data from 258 of the 272 participants (95%). Children wore the MicroPEM for an average of 46% of the 72-h period, and over 80% for a 2-day, 1-night period (with sleep hours counted as non-compliance for this study). Elevated PM2.5 exposures occurred in the morning, evening, and overnight. Median PM2.5, BC, and BrC-ETS concentrations were 8.1 μg/m3, 3.6 μg/m3, and 2.4 μg/m3. The combined BC and BrC-ETS mass comprised 72% of the PM2.5. Woodstove presence, hours used per day, and the primary heating source were associated with the children’s PM2.5 exposure and air filters were associated with reduced PM2.5 concentrations. Our findings suggest that woodstove smoke contributed significantly to this cohort’s PM2.5 exposure. The high sample validity and compliance rate demonstrated that the MicroPEM can be worn by young children in epidemiologic studies to measure their PM2.5 exposure, inform interventions to reduce the exposures, and improve children’s health.